2013
DOI: 10.1021/bi400669h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Functional Roles of Critical Residues in Human Cytochrome P450 Aromatase

Abstract: Cytochrome P450 aromatase (CYP19A1) is the only enzyme known to catalyze the biosynthesis of estrogens from androgens. The crystal structure of human placental aromatase (pArom) has paved the way toward understanding the structure–function relationships of this remarkable enzyme. Using an amino terminus-truncated recombinant human aromatase (rArom) construct, we investigate the roles of key amino acids in the active site, at the intermolecular interface, inside the access channel, and at the lipid–protein boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 32 publications
8
88
0
Order By: Relevance
“…The activity of rArom (55 nmol/min/mg protein) [17] was previously demonstrated to be comparable to the full-length placental and crystallized enzyme [18] as well as other recombinant systems previously developed for the same enzyme [41][42][43][44][45].…”
Section: Effect Of Sildenafil On the Catalytic Parameters Of Rarommentioning
confidence: 74%
See 2 more Smart Citations
“…The activity of rArom (55 nmol/min/mg protein) [17] was previously demonstrated to be comparable to the full-length placental and crystallized enzyme [18] as well as other recombinant systems previously developed for the same enzyme [41][42][43][44][45].…”
Section: Effect Of Sildenafil On the Catalytic Parameters Of Rarommentioning
confidence: 74%
“…This behaviour was assigned to a specific residue (Asp309) by site directed mutagenesis experiments [36]. According to the crystal structure, this residue is involved in a hydrogen bond with the keto-group of the substrate and it is protonated at physiological pH [17,18,36]. For the aromatase inhibitor anastrozole, the K D values variation did not show a linear increasing trend in the pH range 6.5-9.0, indicating that the inhibitor binding does not directly depends on the protonation state of Asp309 in the pH range investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inferences from crystallography suggest protonation of Asp 309 , and theory highlights the potential value of this proton for catalysis, additional experimental evidence is required to support an elevated pK a for Asp 309 in aromatase. In a previous work, using an N-terminally truncated form of human aromatase expressed in Escherichia coli (rArom-WT) 3 and sharing the same structural and functional features of the full-length wild-type enzyme, we found that the mutation of Asp 309 to a non-titratable asparagine residue abolishes aromatase catalytic activity (12). In the present work, we describe the pH dependence of aromatase ligand binding.…”
mentioning
confidence: 76%
“…Theoretical calculations based on one crystal structure (11) and site-directed mutagenesis studies (12) supported the structural data. Furthermore, the crystal structures in complex with androstenedione revealed a close contact (2.7 Å) between the 3-keto oxygen atom of androstenedione and the ␦-O atom of Asp 309 (10,12). Similar distances between these atoms in the crystal structures with exemestane and other steroidal inhibitors have likewise been observed (13).…”
mentioning
confidence: 82%